Criteria for Comparative Literary Analysis in School Literary Studies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Comparative literary analysis is an essential component of literary studies in secondary education. It fosters critical thinking, encourages students to explore literary traditions, and enhances their understanding of diverse cultural and historical contexts. This article explores the criteria for conducting comparative literary analysis within school literary studies, using Jonathan Swift's works - particularly Gulliver's Travels and A Modest Proposal - as a case study. By establishing key criteria such as thematic comparison, stylistic analysis, socio-political critique, and historical context, this article offers a framework for guiding secondary school students in their comparative analysis of literary works. Through these criteria, students can develop a deeper appreciation for both Swift’s writing and the broader scope of literary and historical discourse.